Usability testing of intensive course mobile application using the usability scale system - Manda Rohandi; Nurlaila Husain; Indri Wirahmi Bay (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
The mobile intensive course (MIC) application version 2 is an application created to assist the learning process of the English intensive course. Measurement of the usability of the MIC version 2 application has never been done before, so the effectiveness, efficiency, and user satisfaction for this application have not been measured. In addition, usability measurement can be used as a reference for the level of user loyalty, whether including net promoters, passive users, or detractors. One of the usability measuring tools that are easy to use, the calculation is simple and can be used on a small sample, but still valid and reliable is the System Usability Scale (SUS). The purpose of this study was to test the usability of the MIC version 2 application to determine the quality of this application using the SUS questionnaire. This research was conducted in four steps, namely 1) piloting the MIC version 2 application to the respondents; 2) distributing SUS questionnaires to respondents to be filled out manually or online; 3) calculating the average SUS score; 4) analyzing the mean SUS score. This study involved 37 respondents consisting of students and lecturers of EIC. The results of this study indicate that the usability of the MIC version 2 application can be accepted by users with an average SUS score of 70.61 and get category C based on the CGS assessment. When viewed from the level of user loyalty, the average SUS score for this application only results in passive users. The average value of the contribution to learnability obtained is still low, which is 1.9 from the maximum value of 4. Improvements are needed in future applications in terms of application learnability, such as simplifying the appearance of features and functions in the application, thus allowing users to be more familiar with applications and potential as net promoters.